Reduction Effort of Motion Waste in a Test Room of Component Products - Hadisurya, Kevin; Sutapa, I Nyoman (Jurnal Titra, 2015)
The researchâs goal is to reduce non-value-added motion or activity of a production process, which can be classified as a waste in a production process. The research is done in test room. Non-value-added motion or activity can reduce productivity and slowing production process. Improvement proposal of this research consist of re-layout proposal of test room and implementation of kaizen in test room. Improvement of re-layout in test room resulting in a better design of layout, showing result of reducing total travel distance of material in testing process. The new layout showing moment calculation result of 107196 meters, while the old layoutâs result is 153856 meters. Based on the result, the new layout implemented in test room. Kaizen implementation in test room is done by creating visual control, improvement implemented by creating boundary line of object in test roomâs workplace. Improvement also done by creating a place for storing any tools and equipment that support testing process, with refers to the concept of kaizen foam.